1970
DOI: 10.3329/jafmc.v6i2.7273
|View full text |Cite
|
Sign up to set email alerts
|

Hanging as a Method of Suicide: Retrospective Analysis of Postmortem Cases

Abstract: This retrospective study was conducted on 145 postmortem cases of hanging victims at government medical college morgue over a period of two years. The objective of this study was to find out the pattern of hanging cases as a proper method of suicide and to evaluate the present situation of hanging in this capital city. Out of 145 cases, 41% were male and 51% were married. One hundred and one victims hanged themselves at night, while 44 at day time. In 72 victims, stomachs were found empty. Most (97%) of the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
46
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 9 publications
10
46
2
Order By: Relevance
“…This finding contradict that was found in both the study conducted in Dhaka Medical College and Sir Salimullah Medical College. 9,11 In this study only one case was found above 50 years and no case was above 60 year. It was observed that Dopatta/Orna was the commonest ligature material used for hanging.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This finding contradict that was found in both the study conducted in Dhaka Medical College and Sir Salimullah Medical College. 9,11 In this study only one case was found above 50 years and no case was above 60 year. It was observed that Dopatta/Orna was the commonest ligature material used for hanging.…”
Section: Discussionmentioning
confidence: 53%
“…This study revealed that hanging was the commonest method of suicide in young women, it differs the findings of Lorna Duckworth 10 and quarrel with spouse was the commonest cause of suicidal hanging, this finding corresponds with the study conducted in Dhaka Medical College. 11 Owing to lack of experience of the investigating officers in the field of medico-legal work, the inquest reports prepared by them are usually inadequate and incomplete. These deficiencies lead to difficulty in collection of accurate statistical data such as cause and material used were undetermined in some cases in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Almost similar observations were made by a good number of authors. 12,13,18,19 In present study cyanosis of fingertips and nail beds of both hands was the commonest finding followed by pale, white, hard, and glistening subcutaneous tissue underneath the ligature mark and dribbling marks of saliva. These findings are the most important signs of asphyxia and are mentioned in every literature available.…”
Section: Discussionmentioning
confidence: 96%
“…11,15 Most of the previous studies done in Bangladesh reported similar trend with a negligible exceptions in a few studies. [17][18][19][20] Majority of victims used dopatta (orna) followed by nylon rope, sari and electric wire. Ali et al reported that soft material like orna, saree, and cloth were the preferred material for hanging in their study followed by firm materials like rope.…”
Section: Discussionmentioning
confidence: 99%